If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2x + -3x = 10 Combine like terms: 2x + -3x = -1x 3 + -1x = 10 Solving 3 + -1x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 10 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 10 + -3 -1x = 10 + -3 Combine like terms: 10 + -3 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 35+15x=17x | | fx-gx=hforx | | 3(x+4)+x=(2x-7) | | -2x+2+3x=6 | | 7p-(p+4)=-2(2p-1)+10 | | 3-x+4x=6 | | 5+7x-x=71 | | X+1.5x= | | 7x-7y=5solvey | | 4nsquared+4n-168=0 | | k=gd | | 21x+1=4 | | 6m+6(6m-3)=108 | | 10-5t=6t-23 | | f(x)=ln(e^2x) | | y+3=.5(x-4) | | 16y^8= | | 3x+84=75 | | 72x+9y=18 | | 13x=2(5x+3) | | 9(x+7)+10=11x-2(x-3) | | 24-2x=14x-21 | | 3x^3+8x=420 | | 5b^4=134 | | 5+3(3x-5)=5-4(2x+1) | | 3x^2+8x=420 | | 2cosx=1-sinx | | f(x)=x^3-3x^2-9x+12 | | 0.8(x+300)=0.84x-56 | | 14-x^4= | | 2cos^2x+2cosx-1=0 | | 0.87y+2=y-0.6 |